Feeling at Home in Europe: Migration, Ontological Security, and the Political Psychology of EU Bordering. Issue 6 (12th December 2018) - Mitzen, Jennifer
Abstract : While the EU has long been understood as a postnational political project, stressors like migration have prompted "neo‐Westphalian" responses. For insight into such backsliding, I focus on the concept of home. A psychological need for home as a place of "being" is central to an ontological security approach to subjectivity, and home qualities that resonate psychologically underpin political projects such as the Westphalian homeland. At both levels, home is understood as an enclosed refuge. But home is not necessarily that way, and that monological discourse, which privileges borders, limits our political imagination. To reclaim a plural notion of home, drawing on Winnicott and others, I propose that home is a space of "being with becoming." Scaling up, this makes room for a new macro political idea, homespace. EU migration governance reproduces ideas of the home as homeland. I propose reorienting the imaginary of home to homespace, which focuses on centering and emplacement practices and locales of encounter, to help capture the promise in the EU's post‐Westphalian territoriality.